Awareness and opinions of non‐alcoholic fatty liver disease by hospital specialists. Issue 3 (27th February 2013) - Bergqvist, C.‐J.; Skoien, R.; Horsfall, L.; Clouston, A. D.; Jonsson, J. R.; Powell, E. E.
Abstract Background/Aim Subjects with metabolic risk factors for non‐alcoholic fatty liver disease (NAFLD) are commonly seen by hospital specialists other than gastroenterologists/hepatologists. The aim of this study was to assess the awareness of NAFLD and opinions regarding management among non‐hepatologists at two major tertiary hospitals in Brisbane. Methods A face‐to‐face questionnaire assessing current beliefs and practices regarding NAFLD was administered to specialists and specialists‐in‐training across six specialties (internal medicine, cardiology/cardiac surgery, endocrinology, thoracic medicine, rheumatology and nephrology). Results One hundred clinicians were surveyed with 99% returning completed questionnaires (>89% questions answered). The majority of respondents (75%) believe the prevalence of NAFLD in the general population to be ≤10%, although two‐thirds feel that its incidence will rise markedly. The vast majority (>90%) appreciate that traditional cardiovascular risk factors (obesity, hypertriglyceridaemia and diabetes) are risk factors for NAFLD and acknowledge that these are common in non‐hepatology patients. Despite this, most believe that NAFLD is uncommon in their own patients (89% indicated a prevalence ≤30%). The vast majority (93%) agree that non‐alcoholic steatohepatitis (NASH) is associated with increased overall mortality, but 60% also believe that simple steatosis confers increased liver‐related mortality. Most (74%) agree that a diagnosis of NASH cannot be made using liver enzymes, but 67% support 6‐monthly liver function tests as the most effective way to monitor progression of NAFLD. Most respondents (71%) make no referrals to hepatology for suspected NAFLD. Conclusions Non‐hepatologists appreciate the seriousness of NAFLD but appear to underestimate its prevalence, especially among their own patients despite known risk factors. Attitudes regarding simple steatosis versus NASH and appropriate monitoring of suspected NAFLD suggest that more can be done to improve the understanding of this disease among non‐hepatologists. This has implications for targeting 'at‐risk' populations and appropriate referral of patients to hepatology clinics.